Factors Causing Fraudulent Management of Village Funds During the COVID-19 Pandemic - Manuhara, Wahyu; Sani, Mar’atussholichah Kurnia; Putra, Adli Zuliansyah; Utami, Budi Barata Kusuma (Journal of Accounting and Investment, 2024)
Research aims: This study examines the factors that cause fraud in managing village funds during the COVID-19 pandemic, including financial pressure, supervision, rationalization, competence, apparatus position power, and transparency.Design/Methodology/Approach:   Four hundred and five respondents who were village officials in four provinces were involved based on the convenience sampling method. Respondents were given seven days to fill out the questionnaire, and then the data were analyzed using SEM-PLS.Research findings:    Several factors can lead to fraudulent management of village funds during the COVID-19 pandemic: financial pressure, rationalization, and position power. Meanwhile, transparency significantly negatively affects the fraudulent management of village funds during the COVID-19 pandemic.Theoretical contribution/Originality:  The research contributes to developing the fraud pentagon theory by presenting the arrogance dimension proxied using the power of position in the context of village government during the COVID-19 pandemic.Practitioner/Policy implication: This research is expected to be an input for the village government in developing mechanisms that can prevent fraud in managing village funds using the dimensions in the fraud pentagon theory.Research limitation/Implication:   The scope of the research used is relatively small, only covering village governments from nine districts in four provinces in Indonesia. Thus, caution is needed in generalizing the results. Therefore, a wider population is needed.